Identification of Novel ROS Inducers: Quinone Derivatives Tethered to Long Hydrocarbon Chains - Hong, Yeonsun; Sengupta, Sandip; Hur, Wooyoung; Sim, Taebo (AMER CHEMICAL SOC, 2015)
We performed the first synthesis of the 17-carbon chain-tethered quinone moiety 22 (SAN5201) of irisferin A, a natural product exhibiting anticancer activity, and its derivatives. We found that 22 is a potent ROS inducer and cytotoxic agent. Compound 25 (SAN7401), the hydroquinone form of 22, induced a significant release of intracellular ROS and apoptosis (EC50 = 1.3-2.6 mu M) in cancer cell lines, including A549 and HCT-116. Compared with the activity of a well-known ROS inducer, piperlongumine, 22 and 25 showed stronger cytotoxicity and higher selectivity over noncancerous cells. Another hydroquinone tethering 12-carbon chain, 26 (SAN4601), generated reduced levels of ROS but showed more potent cytotoxicity (EC50 = 0.8-1.6 mu M) in cancer cells, although it lacked selectivity over noncancerous cells, implying that the naturally occurring 17-carbon chain is also crucial for ROS production and a selective anticancer effect. Both 25 and 26 displayed strong, equipotent activities against vemurafenib-resistant SK-Mel2 melanoma cells and p53-deficient H1299 lung cancer cells as well, demonstrating their broad therapeutic potential as anticancer agents.
Keywords: CANCER-CELLS; OXIDATIVE STRESS; APOPTOSIS; ACTIVATION; MECHANISM; AKT; VEMURAFENIB